AI-Generated Media Perception and AI Attitudes among Gen Z: The Mediating Role of Digital Literacy - Batool, Marwa; Bashir, Shamshad (ACADEMIA International Journal for Social Sciences, 2026)
The rapid development of artificial intelligence has had a major impact on the creation and consumption of digital content and especially with the advent of AI-created media. This change is affecting the way youth consumers perceive online information and form their opinion of the artificial intelligence technologies. The current research sought to explore how the world of perception of AI-generated media and the attitude to artificial intelligence among Generation Z are connected. The paper also investigated whether digital literacy mediates this relationship. In particular, the study examined the hypotheses that the capacity of the individuals to critically interpret digital content can be viewed as the reason why their attitudes to AI-generated media shape their attitude towards artificial intelligence. This study incorporated a quantitative correlational research design. The research was performed among 300 Generation Z students of public and private universities in Lahore, Pakistan (M = 21.95, SD = 2.41). The perception AI-generated media, digital literacy and attitudes towards artificial intelligence were measured using standardized and reliable measure scales. The data were broken down in SPSS version 26 and PROCESS macro by Hayes. Some of the statistical methods used were descriptive statistics, Pearson correlation, mediation analysis, independent samples t-tests, and one-way ANOVA to test the relationships between variables and demographic differences. The findings revealed that the attitude towards artificial intelligence among the participants of Generation Z depended on perceptions of AI-generated media significantly. Also, digital literacy was positively related to attitudes toward artificial intelligence statistically significantly. The mediation analysis however showed that media perception as generated by AI did not significantly predict digital literacy. Therefore, the mediating effect of digital literacy was not found in the correlation between AI-generated media perception and opinions about artificial intelligence. According to these findings, despite the fact that digital literacy plays a role in developing positive attitudes towards artificial intelligence, the impact of artificial intelligence media perception on artificial intelligence attitudes is more of a direct relationship and not of an indirect relationship of mediating process. The relevance of this research in practice is found in the fact that, in order to teach young people how to find a critical approach toward emerging AI technologies, it is necessary to reinforce the digital literacy education. The originality of this study will be to investigate the direct correlation between media perception of AI-generated media and attitudes towards artificial intelligence as well as the possibility that digital literacy serves as the mediating variable between Generation Z, which has a high exposure to fast-evolving AI-driven media settings.